Patterns Of Law Enforcement Against Premeditated Murder - Tirtaraharja, Pirman; Hilman, Didi; Hartini, Sri (JURNAL MAHASISWA YUSTISI, 2023)
The strategy used in this research is unmistakable Examination, which is a critical thinking method that is concentrated on interpreting information obtained from the field both from essential information and optional information obtained from writing and field studies, while the procedure for selecting information is carried out by perception and encounter. From the consequences of the review, the creator surmised that the elements that cause premeditated murder are: 1. Monetary and Social Elements, Family Variables, Mental Elements, and Ecological Variables. Guidelines for Criminal Regulations on Examples of Requirements How the guidelines for Criminal Regulations against Perpetrators of Planned Murder in the Criminal Code, Law, Islamic Regulations and Standard Regulations are unique, Assuming the Criminal Code is according to Article 340 of the Criminal Code, If according to the Statute contains guidelines Criminal regulations against perpetrators of planned murder depend on the choice of past judges by examining and considering similar cases, based on Islamic regulations in the event that a person commits premeditated murder, he will be punished by the qisash regulations, and according to standard regulations assuming a person commits premeditated murder, he will be punished according to customary customs for each local which is completely in accordance with the traditions and customs of the area.